Effects of the COVID-19 crisis on work-life balance, mental health, and perceived health status among Hungarian defense employees: a cross-sectional study - Evelin Trembeczki; Manuela Tvaronavičienė; János Besenyő; István Kobolka (Journal of Business Economics and Management)
The COVID-19 pandemic impacted profoundly on the mental and physical health of defense personnel, due to their involvement in the enforcement of COVID-19 measures and confined work environments. This cross-sectional study assessed the effects of the pandemic on work-life balance, mental health, and perceived health status among Hungarian defense employees. Data was collected from 300 employees of a Hungarian defense company using an online questionnaire that included demographics, work-related observations, mental health scales (DASS), and perceived health status (SF-12). Data was analyzed using descriptive and inferential statistics. The results indicated that work type, flexibility, and workload remained stable before, during, and after the pandemic. Compensation satisfaction (p = 0.025) showed a slight increase post-COVID-19, while organizational support did not significantly change (p > 0.05). Work-life balance significantly decreased during the pandemic (p = 0.012), and the mental health indicators stress (p = 0.005), anxiety (p < 0.001), and depression (p < 0.001) increased significantly. Reliability analysis (Cronbach’s alpha) demonstrated good internal consistency across the scales. These findings underscore the significant negative impact of the COVID-19 pandemic on the mental health of defense employees, reinforcing the need for sustained support mechanisms to promote both physical and mental well-being in this workforce.